Understanding race in intersectionality with childhood. The use of the skin-colored pencil when painting the negritud - María Isabel Mena G (University of Bologna, 2024)
This research article is the result of the doctoral thesis on the construction of racial identity in black children in Colombia; to experiment with the self-application of body tones, it used child drawing as a narrative of the first order that allowed identifying patterns through the representation of the body. Here the school emerges with force, since it is the place where the skin, flesh or natural color is used as a prototype when painting the human body, so that it is a device deeply rooted in school culture. Methodologically, the researcher constructed a spontaneous qualitative-based experiment to demonstrate that through the use of skin color black children create a strong contradiction in their identity process. As a fragment of the thesis, this article recounts the findings of a case study, given that most of the faces of black childhoods were painted skin-colored, then urgent action must be taken to establish the consequences for a healthy racial consciousness.